A cohort study showing correspondence of low wall shear stress and cephalic arch stenosis in brachiocephalic arteriovenous fistula access. Issue 3 (May 2021) - Hammes, Mary; Cassel, Kevin; Boghosian, Michael; Watson, Sydeaka; Funaki, Brian; Coe, Frederic
Background: A brachiocephalic fistula is frequently placed for hemodialysis; unfortunately, cephalic arch stenosis commonly develops, leading to failure. We hypothesized that a contribution to brachiocephalic fistula failure is low wall shear stress resulting in neointimal hyperplasia leading to venous stenosis. The objective of this investigation is to determine correspondence of low wall shear stress and the development of cephalic arch stenosis. Methods: Forty subjects receiving hemodialysis with a primary brachiocephalic fistula access were followed from time of placement for 3 years or until cephalic arch stenosis. Venogram, Doppler, and viscosity were performed at time of fistula maturation, annually for 3 years or to time of cephalic arch stenosis. Computational hemodynamics modeling was performed to determine location and percent low wall shear stress in the arch. The relationship between wall shear stress at time of maturation and location of cephalic arch stenosis were estimated by correlating computational modeling and quadrant location of cephalic arch stenosis. Results: In total, 32 subjects developed cephalic arch stenosis with 26 displaying correspondence between location of low wall shear stress at time of maturation and subsequent cephalic arch stenosis, whereas 6 subjects did not (p = 0.0015). Most subjects with correspondence had low wall shear stress areas evident in greater than 20% of the arch (p = 0.0006). Low wall shear stress was associated with a higher risk of cephalic arch stenosis in the 23-to-45 age group (p = 0.0029). Conclusions: The presence and magnitude of low wall shear stress in the cephalic arch is a factor associated with development of cephalic arch stenosis in patients with brachiocephalic fistula. Attenuation of low wall shear stress at time of maturation may help prevent the development of cephalic arch stenosis which is difficult to treat once it develops.